Peran Komisi Pengawas Persaingan Usaha (Kppu) Kantor Wila yah V Balikpapan Dalam Penyelesaian Pelanggaran Persaingan Usaha Di Kalimantan Timur (Studi Kasus Putusan Kppu Nomor 17/Kppu-L/2016) - Wahyuni Safitri; Heidy Olha Wuaten (Law Department, University of Widya Gama Mahakam Samarinda, 2020)
The role of the Business Competition Supervisory Commission (KPPU) of Regional Office V Balikpapan is to create a Healthy Business Competition Climate in East Kalimantan.The practice of fraud in the tender process in the implementation of procurement of government goods / services can be in the form of conspiracy. Business Competition Supervisory Commission (KPPU) as supervisor of business competition based on Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition has the task of supervising the prohibition of conspiracy in tenders as stipulated in article 22 of Law Number 5 of 1999, One of which is to decide breach of tender conspiracy in this case the case that has been handled by the KPPU of the Balikpapan Regional Representative Office namely Case Number 17 / KPPU-L / 2016 concerning Alleged Violations Article 22 of Law Number 5 of 1999 concerning Improvement of the Jongkang Road to Jakarta Samarinda Samarinda Karang Paci Road (Ring Road III) Tenggarong Seberang District. The method used in this study is normative juridical supported by field research, namely the Business Competition Supervisory Commission (KPPU) Regional Office V Balikpapan. The results of the study based on the case verdict showed that the KPPU of the Balikpapan Representative Office had successfully handled this case so that they had sentenced each Reported Party I, and 2 They had sentenced each Reported Party I, and 2 PT Karyatama Nagasari as Reported Party I and PT Jasin Effrin Jaya as Reported Party II, to pay a fine of Rp. 5,021,028,000.00 (Five Billion Twenty One Million Twenty Eight Thousand Rupiah) which must be deposited to the State Treasury, and Prohibit PT Karyatama Nagasari as Reported Party I and PT Jasin EffinJaya as Reported Party II to participate in the tender in the field of road construction services for 2 (two) years in all regions of Indonesia.